The teaching management and study of Hadith: method, contents, and approaches - MUKHIBAT, M (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The shift in the orientation of Hadith studies in Indonesia and the West has given rise to differences in the aspects of the method, the material and its approach, and the management of learning. These differences have given rise to different study models. The question is how the study model is appropriate in the Indonesian context. Based on this qualitative-collaborative research at UIN Jakarta and the Oxford Oriental Institute, it is hoped that there will be renewal in the methods and approaches of the study of Hadith in Indonesia. RESUMEN El cambio en la orientación de los estudios Hadith en Indonesia y Occidente ha dado lugar a diferencias en los aspectos del método, el material y su enfoque, y la gestión del aprendizaje. Estas diferencias han dado lugar a diferentes modelos de estudio. La pregunta es cómo el modelo de estudio es apropiado en el contexto indonesio. Sobre la base de esta investigación cualitativa y colaborativa en UIN Jakarta y el Oxford Oriental Institute, se espera que se renueven los métodos y enfoques del estudio de Hadith en Indonesia.